2011
DOI: 10.21608/jpp.2011.85760
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Studies on Jerusalem Artichoke 1- Productivity and Quality of Jerusalem Artichoke in the New Reclaimed Lands.

Abstract: A field experiment was carried out in sandy soil in EL-Kattba, Manofya Governorate Egypt, during the successive growing seasons of 2007 and 2008 on Jerusalem artichoke. The main objective of this investigation was to study the effect of cultivars (Local and Fusaeu) and two planting dates(15 th April and 15 th May) with two harvesting dates (15 th Nov. and 15 th Dec.) on vegetative growth , total yield , marketable yield and its components of Jerusalem artichoke. The results indicated that Local cultivar showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 5 publications
3
2
0
Order By: Relevance
“…These differences in the concentrations of total phenolic compounds and total flavonoids may be due to genetic differences among both Jerusalem artichoke varieties according to Kapusta et al (2013). The obtained results were in agreement with those obtained by Neama et al (2020) who noted that the Fuseau variety is superior to the Balady variety in phytochemical, and inulin contents, Attia (2011), Alian, andIsmail (2014) reported that inulin, total sugar, and reducing sugars of both tubers ranged from (22.15%, 24.21%), (8.64%, 10.03), (22.31%, 23.78%), (6.28%, 10.15%) for Balady and Fuseau varieties, respectively. It is noteworthy that inulin (which belongs to a class of dietary fibers known as fructans) is well fermented by gut bifidobacteria, which contributes to their anticarcinogenic properties.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…These differences in the concentrations of total phenolic compounds and total flavonoids may be due to genetic differences among both Jerusalem artichoke varieties according to Kapusta et al (2013). The obtained results were in agreement with those obtained by Neama et al (2020) who noted that the Fuseau variety is superior to the Balady variety in phytochemical, and inulin contents, Attia (2011), Alian, andIsmail (2014) reported that inulin, total sugar, and reducing sugars of both tubers ranged from (22.15%, 24.21%), (8.64%, 10.03), (22.31%, 23.78%), (6.28%, 10.15%) for Balady and Fuseau varieties, respectively. It is noteworthy that inulin (which belongs to a class of dietary fibers known as fructans) is well fermented by gut bifidobacteria, which contributes to their anticarcinogenic properties.…”
Section: Discussionsupporting
confidence: 93%
“…When compared to other interactions, it was noted that plants of the Fuseau variety gave a significant increase in the tuber weight of the plant in the second season only. These results were according to those reported by Alian and Attia (2011). Whereas it was noticed that there were increases in tuber weight in the Fuseau plants' variety when compared to the Balady plant's variety.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations